Archaeological Landscape of Mayong in the Kalang-Kapili Valley of Assam - Manjil Hazarika; Shiela Bora; Y. S. Sanathana (Ancient Asia, 2022)
Mayong in Morigaon district of Assam is known as a land of black magic, witchcraft, sorcery and tantric practices, spiritual healing and indigenous medicinal system since the medieval period. The area is also extremely rich in terms of archaeological remains and sites of historical importance. With an objective of documenting and mapping the archaeological landscape of the region, an extensive field survey was undertaken during 2020–21. This survey has resulted in the discovery of diverse archaeological remains including polished stone tools, early and late medieval rock-cut sculptures and temple ruins, specimens of sculptures belonging to the Pala-Sena period, archaeological mounds with pottery, brick and terracotta architectural pieces, metal objects belonging to Vajrayana religious sect, inscriptions, engravings, mason marks, ancient stone quarrying, battle ground, ramparts, cannons and cannon balls, water tanks, manuscripts, bronze and bell metal sculptures, Vaishnavite 'Satras' (monasteries), 'Naamghars' (prayer halls) and 'Thans' (sacred places). This paper discusses these archaeological remains and their relevance for understanding the ancient cultural development in Mayong and the Kalang-Kapili Valley.